Analysis of absorption time delays in streaking of resonant and non-resonant two-photon ionization. (6th July 2018) - Goldsmith, C; Su, J; Jaroń-Becker, A; Becker, A
Abstract: We theoretically study the determination of the time delay between the subsequent absorption of photons in two-photon ionization with the attosecond streaking technique. An analytical model for the absorption time delay based on analysis of the process using perturbation theory is obtained. Model predictions at central frequencies that are resonant and non-resonant with an intermediate bound state agree well with results of numerical streaking simulations, if the intermediate state is well-isolated from other states and the effect of the streaking field on the intermediate state is negligible.